Social Representations in Street-Level Bureaucracies – Production and Reproduction of Knowledge Within Public Administration - Brauer, John; Johansson, Björn; Bruhn, Anders (Scandinavian Journal of Public Administration, 2021)
The concept of street-level bureaucracy is central to understanding public administration because it pinpoints the role of individual civil servants in the realization of policy. An issue in need of further illumination is that of knowledge production and reproduction in street-level bureaucracies. This article seeks to examine these issues by linking street-level bureaucracy with the theory of social representations. Social representations offer a social-psychological understanding of how individuals make sense of their reality in day-to-day interaction. The aim of this article is to describe and demonstrate how an integration of these two concepts can enrich the analysis of street-level bureaucracies. The synthesis is also demonstrated by presenting an analysis of social representations of unemployment among two groups of street-level bureaucrats.